Expansion and Specialization of Agricultural Systems in Western Mediterranean Areas: A Global Analysis Based on the Two Last Census Data - Marya Rabelo; Marta Debolini; Ricardo Villani; Tiziana Sabbatini; Nicola Silvestri (Agronomy, 2021)
The study aims to describe and interpret the agricultural system dynamics on the Western Mediterranean areas in terms of occupied land and crop specialization, by using the available data from the two last agricultural censuses. From the spatial point of view, we chose to adopt the most detailed level available, by using the smallest land administrative unit (LAU) for every involved country (Spain, Portugal, France and Italy). The resulting database was made of about 16k records and seven fields for a total of 112k single data. The considered variables were: total farm area (TFA), utilized agricultural area (UAA), irrigated area (IA), arable lands (AL), permanent crops (PC), permanent grassland (PG) and remaining surface (RS). The LAU data analysis was carried out following the four steps: (i) level of land occupation by agricultural systems; (ii) patterns of crop groups in UAA composition; (iii) attribution to each LAU of an agricultural typology (AT), resulting from the combination of the two previous features and iv) calculation of two synthetic indices to evaluate the expansion and specialization level for each LAU. Finally, an analysis of the spatial distribution of the two indices was proposed. Results showed a lowering over time of the TFA, UAA and PG areas and an increase of IA and RS. The number of identified ATs was rising at the expense of their extension. This phenomenon led to a fragmentation in ATs spatial distribution within the same geographical region. These changes prove that farmers’ responses to the driving forces acting on agricultural systems have been more differentiated than in the past. The prevailing strategy seems to aim at a reduction in the level of specialization of the agricultural systems whereas less marked was the lowering of their level of expansion.